Off the rim basketball and other religions in a Carolina childhood - Hobson, Fred C., 1943- (Sports and American culture series., 2006)
"Hobson, a passionate follower of North Carolina basketball who once played briefly for the Tar Heels, tells the story of an eternal childhood relived each season. More than a basketball memoir, his account also depicts a seldom-viewed South through glimpses of a boyhood in the Carolina hills"--Provided by publisher.